Eufemisme Netizen dalam Menanggapi Konten Parenting di YouTube Nikita Willy: Tinjauan Sosiolinguistik - Laila, Nur Rizka; Nuryani (Universitas Muhammadiyah Surakarta, 2025)
The phenomenon of using softened and indirect language in digital communication has drawn attentionin sociolinguistic studies, particularly in the context of netizen comments on public figures. This studyaims to identify the forms and functions of euphemisms employed by netizens in response to parentingcontent on Nikita Willy's YouTube channel. Utilizing a qualitative descriptive method and discourseanalysis approach, the data were drawn from 30 purposively selected netizen comments. The analysisof euphemism forms is based on the classification proposed by Allan and Burridge, while the functionsare examined using Burridge’s framework. The results show that eight types of euphemisms werecommonly used: metaphor, figurative expression, colloquialism, abbreviation and acronym,circumlocution, jargon, omission, and one-for-one substitution. Among these, figurative expressionsappeared most frequently. In terms of function, the euphemisms identified serve protective, cohesive,booster, deceitful, and humorous purposes. These findings suggest that netizens tend to useeuphemisms as a linguistic strategy to maintain politeness, foster solidarity, and convey criticism subtlyin discussions around parenting an issue laden with values and social norms. This research contributesto a deeper understanding of language dynamics in digital public spaces, especially in parentingdiscourse involving female public figures.